Recent Advances in Catalytic Condensation Reactions Applications of Supported Ionic Liquids - Yao, Nan; Wu, Ya P.; Zheng, Kai Bo; Hu, Yu Lin (Current Organic Chemistry, 2018)
Background: Condensation reactions have attracted increasing attentions due to their important organic transformations in a wide variety of fields of organic chemistry. The main limitations of conventional methods are urgently needed for the development of efficient and heterogeneous catalytic systems. Objective and Method: Supported ionic liquids have broad applications in catalytic reactions due to their significant properties such as wide range of temperature, excellent thermal stability, negligible volatility, high ionic conductivity, and high surface area with a remarkable level of catalytic performance. Moreover, due to their heterogeneous properties, they have the attractive features of easy separation and recyclability. In this review, we highlight the critical role of supported ILs as green heterogeneous catalysts in catalytic condensation reactions such as Aldol condensation reaction, Biginelli reaction, Knoevenagel condensation and other condensation reactions. Results: Different supported ILs having highly promising future prospects in the field of condensation reactions have been investigated. Their applications in condensation reactions possess attractive features such as high efficiency, easy separation from the reaction mixture and excellent recyclability. Conclusion: The versatilities and adaptabilities of supported ILs in various condensation reactions are considered as a powerful research field in these transformations. It should be certain that this kind of supported IL materials will play an important role in condensation reactions and other organic reactions in the near future.
Keywords: Supported catalysts